STUDY ON THE DESIGN OF CONTROL THROUGH SEVEN SEGMENT PARALLEL PORT - Hardiyan Hardiyan; Luyung Dinaini, SKom, MM (Jurnal Sistem Komputer, 2004)
Utilization through the parallel port interface can help the computer in supporting the process of transferring data linking with other peripherals such as seven-segment. With a seven-segment control, can display the meter reading or digital data that is controlled seven-segment on Digital To Analog Converter (DAC). Views process scanning process can use. It would be more effective and efficient port is used for transferring data within a range of doing that is not too green. it is also more cost-effective compared with the manufacture of Programmable Peripheral Interface Card Interface 8255.